2016
DOI: 10.1210/en.2015-1820
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Experimental Arthritis and Associated Bone Loss by a Tissue-Selective Estrogen Complex

Abstract: In addition to the systemic inflammation present in rheumatoid arthritis (RA), decreased estradiol levels in postmenopausal RA patients further accelerate bone loss in these patients. The tissue-selective estrogen complex (TSEC), an estrogen combined with a selective estrogen receptor modulator, is a new hormone replacement therapy option. The first approved TSEC, containing conjugated estrogens and bazedoxifene (BZA), reduces menopausal symptoms and prevents osteoporosis with an improved safety profile compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
3
14
0
1
Order By: Relevance
“…Therefore, selective estrogen receptor modulators (SERMs) were developed to prevent their side effects. Recent studies reported that SERMs inhibit joint inflammation and osteoporosis in female CIA animal models [ 43 , 44 ]. Further experiments are needed to evaluate the effects of SERMs in the SpA mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, selective estrogen receptor modulators (SERMs) were developed to prevent their side effects. Recent studies reported that SERMs inhibit joint inflammation and osteoporosis in female CIA animal models [ 43 , 44 ]. Further experiments are needed to evaluate the effects of SERMs in the SpA mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Postmenopausal osteoporosis is a disease characterized by bone loss and microarchitectural deterioration leading to bone fragility and an increased risk of fracture. 1 The latest data 2 suggests that inflammation plays a critical role in bone remodeling and in pathogenesis of osteoporosis. The present study 3 describes the neutrophil as a cell that acquires roles beyond that of a prototypic inflammatory cell, directly capable of activating osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…ER and PR are critical factors mediating the reproductive activity [29]. These two factors are extensively expressed in whole layers of uterus.…”
Section: Discussionmentioning
confidence: 99%